Pengaruh Kualitas Pelayanan dan Customer Relationship Management Terhadap Loyalitas Pelanggan Dimediasi Kepuasan Pelanggan pada Perusahaan Pelayaran Nasional - Imaduddiin, Humam; Saputra, Datep Purwa; Abdurachman, Edi; Farisyi, Sofwan (Dinasti Research, 2025)
In shipping industry like in PT Kemala Shipping, service quality includes ship condition, schedule reliability, and onboard ship services, whereas Customer Relationship Management manages customer interaction, including scheduling and complaint handling. PT Kemala Shipping faces such problems as no on-schedule ship availability and technical issues that disrupt customer experience as well as inability to handle complaints making the situation worse.. Customer Relationship Management often needs to be integrated with other systems such as ship management systems, booking systems, and financial systems, but PT Kemala Shipping has limited integration systems that cause inconsistent or fragmented data. The objectives of this study include analyzing the direct and indirect effects of Customer Relationship Management and service quality on customer loyalty mediated by customer satisfaction.The research method used path analysis with a sample of 97 ship charterers at PT Kemala Shipping, and through a nonprobability sampling approach with Saturated Sampling. The results of this research indicate that customer satisfaction can mediate the influence of Service Quality and Customer Relationship Management on customer loyalty